Journey to the South: Chinese Buddhist Missions to South and Southeast Asia, 1930s-1945 - Ng, Xiang-Yun (Journal of Chinese religions, 2025)
During the Second Sino-Japanese War (1937-1945), Chinese Buddhist leaders traveled abroad on several occasions to garner support for China's cause. Yet scholarship on twentieth-century Chinese Buddhism or wartime China has paid little attention to this aspect of Buddhist war involvement. This article seeks to address this gap in literature. It examines Yuanying's 圓瑛 (1878-1953) fundraising trip to Singapore and Malaya from 1937 to 1938 and Taixu's 太虛 (1890-1947) journey to South and Southeast Asia from 1939 to 1940 and argues for a broader picture of Buddhist diplomacy supported by the Kuomintang 國民黨 (KMT). In response to funding constraints in China, Japanese propaganda concerning the state of Buddhism in China, and the need to secure support in countries with substantial Buddhist populations, Chinese Buddhists and the KMT collaborated to organize overseas missions that deserve a place in discussions on wartime China's foreign policy.